REKONSEPSI MAKNA PENGANCAMAN KEKERASAN ATAU MENAKUT-NAKUTI DALAM UU ITE - Saiful Abdullah (RechtIdee, 2022)
The development of information and communication technology brings positive and negative influences. The use of information and communication technology, on the one hand contributes to the improvement of human welfare and civilization, which will have a very bad impact. Therefore, ITE the law also regulates criminal law especially regarding criminal acts. On April 21, 2008 has been officially promulgated, Law on Information and Electronic Transactions (ITE). However, in article 29 of the ITE law, the formulation is less clear, namely “threats of violence or intimidation”. Giving rise to different interpretations and the need for changes to be made. This is not in accordance with the principle of lex certa, which means that the formulation of a law must be interpreted firmly without analogy. Article 29 of the law on information and Electronic Transaction, “Any person intentionally and without rights send information, document and/or electronic messages containing threats of violence or intimidation that are intended personally, and cause fear and actually occur violence”